Some Recent Developments in the Theory of Economic Growth: An Interpretation - Britto, Ronald (Journal of Economic Literature, 1973)
I am indebted for helpful comments on earlier versions of this paper to Akira Takayama and Gerhard Tintner. Valuable suggestions concerning style and substance have been made by William A. Brock, Bryan Ellickson and Gilles Paquet. Since some of the issues raised in the recent literature have been-and still are-highly controversial, I must strongly emphasize that all responsibility for the vietvs expressed and the interpretations ogered rests with me alone.